Stances of Imam Al-Rassas (656 A.H.) on the Scholars’ Sayings between Influence and Ijtihad in His Book Jawharat al-Usul and Tadhkirat al-Fuhul in the Foundations of Jurisprudence - Mariam Salim Mohammed,; . Iman Mousa Farhan, (Islamic Sciences Journal, 2025)
This study explores the positions adopted by Imam al-Rassas (may Allah have mercy on him) in his seminal work Jawharat al-Usul and Tathkirat al-Fuhul, highlighting his engagement with the opinions of earlier scholars, especially his grandfather al-Hasan al-Rassas and Imam al-Mansur bi-Allah. The research reveals that Imam al-Rassas was not merely an imitator, but rather a scholar who exercised independent reasoning (ijtihad) and preference (tarjih), sometimes agreeing with and other times opposing the views of his predecessors based on established methodological principles. The study also uncovers areas of mutual influence between Imam al-Rassas and prominent Zaydi scholars, where his views often aligned with those of Imam al-Mansur Billah on issues such as analogy-based specification (takhsis bi al-qiyas) and the definition of transmitted reports (khabar), while differing with him in other areas, such as the immediacy of commands. Additionally, the research addresses points of agreement between Imam al-Rassas and the majority of scholars in usul al-fiqh, particularly on matters like the permissibility of clarification through action, the authority of solitary reports (khabar al-wahid). Conversely, he diverged from them on issues including the necessity of notification in abrogation and stipulating the necessity of explicit clarity in expression. The research concludes by examining Imam al-Rassas's influence on subsequent Zaydi scholars, noting the limited presence of his views in later works on jurisprudential principles, despite his significant scholarly status during his time.